2003
DOI: 10.1002/app.12791
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation and sedimentation of cane sugar juice particles with cationic homo- and copolymers

Abstract: Rapid flocculation and sedimentation of suspended particles in primary cane sugar juice is achieved using a high molecular weight anionic polymer flocculant. This work reports on efforts to enhance the performance of an anionic flocculant by the addition of cationic polymers. Homopolymers of poly(trimethylammonium ethyl methacrylate chloride) (TMAEMAC) and cationic copolymers of poly(trimethylammonium ethyl acrylate chloride) (TMAEAC) and acrylamide were synthesized and their performance, to enhance the floccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Addition of PAC to sorghum juice reduced the turbidity to 93.12 % ± 0.50 %. The effectiveness of PAC in clarifying sorghum juice is found to be relatively similar with previous study on sugar cane juice [9,10]. This is mainly due to the similarity of insoluble impurities between sugar cane juice and sweet sorghum juice.…”
Section: Sorghum Juice Clarificationsupporting
confidence: 76%
See 2 more Smart Citations
“…Addition of PAC to sorghum juice reduced the turbidity to 93.12 % ± 0.50 %. The effectiveness of PAC in clarifying sorghum juice is found to be relatively similar with previous study on sugar cane juice [9,10]. This is mainly due to the similarity of insoluble impurities between sugar cane juice and sweet sorghum juice.…”
Section: Sorghum Juice Clarificationsupporting
confidence: 76%
“…Clarification using liming method produces solid matrix that trap suspended solid as larger particles, which then settled by the mean of gravity. The process was conducted in slightly higher temperature than previous study [9], as it was confirmed that best juice quality was obtained when liming were conducted at temperature of 76 o C to 100 o C. This liming process reduces the turbidity of sorghum stalk juice to 82.43 % ± 0.50 %, measured by reduction of absorbance at 600 nm. The clarified sorghum juice is slightly paler in colour, while small amount suspended particle is still observable at bottom part of container.…”
Section: Sorghum Juice Clarificationmentioning
confidence: 90%
See 1 more Smart Citation
“…These precipitated calcium phosphate microfloc particles act as a sweep flocculent in the clarifier, removing suspended matter from the juice and adsorbing dissolved molecules and ions. The settling rate and efficiency improvement of separation of the liquid-solid system can be carried out by bridging mechanism and charge-patch mechanism [22].…”
Section: Cane Sugar Juice Clarification Processmentioning
confidence: 99%
“…Griebel et al [10,11] has characterized its solution properties and structure-property relationships. There are many reports on using this copolymer as primary flocculant or flocculant aid in clarification of industrial wastewater, separation of solid-liquid systems, dewatering of sludge, and so forth [12][13][14]. However, to our knowledge, studies on its application in decolorization of water-soluble anionic dyes were rare [9], and no report on its binding mechanism to dyes was found.…”
Section: Introductionmentioning
confidence: 97%